MONOPOLY GAME TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Dellarosa, Maretha; Nafisah, Durrotun (Journal of Contemporary Issue in Elementary Education, 2024)
Based on preliminary research, results demonstrated that the learning process in the fifth grade still uses conventional teaching methods without using interactive learning media. This research aims to develop Monopoly Game learning media on biodiversity topics by using Research and Development (R&D), ADDIE model. This model consists of five stages: analyzing, designing, developing, implementing, and assessing. The subjects of the current research were fifth graders at a public elementary school in East Java province, Indonesia. Data collections included media and learning device validation sheets, observation during learning activities, and students’ test results. The data obtained was analyzed by using Likert Scale, especially on validation data and test results to determine the evaluation of the result of media use. From the validation expert, the result shows that the Monopoly game received 81.82% and 80.77% which was included in the very feasible category. Based on the results of students’ learning outcomes, it is proven that the influence of Monopoly media significantly improved the students’ learning outcomes, by 40.09% compared to conventional teaching which was only able to increase their grade by 31.02%. The results emphasize that monopoly learning media improves students' learning outcomes.